1986
DOI: 10.3109/00016348609157352
|View full text |Cite
|
Sign up to set email alerts
|

The Pelvic Outlet: A Comparison Between Clinical Evaluation and Radiologic Pelvimetry

Abstract: A random sample of 798 primiparas was screened with clinical evaluation and radiologic low-dose pelvimetry of the pelvic outlet. The purpose was to study the accuracy of clinical evaluation in comparison with X-ray pelvimetry and to determine whether clinical evaluation could reveal any other factor influencing labor. A significant agreement between clinical and X-ray pelvimetry was found, but the sensitivity of clinical evaluation was low and as many as half the patients with a contracted pelvis, according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…Prior studies have demonstrated the difficulties with utilizing clinical pelvimetry in clinical management, including its low sensitivity for defining a contracted pelvis and low influence on clinical management. 15, 16 Studies of maternal short stature (defined as <155-cm) demonstrate an increased risk for cesarean, but the vast majority (>75%) of these women still deliver vaginally. 1719 Several studies of maternal foot size have found no correlation to mode of delivery.…”
Section: Commentmentioning
confidence: 99%
“…Prior studies have demonstrated the difficulties with utilizing clinical pelvimetry in clinical management, including its low sensitivity for defining a contracted pelvis and low influence on clinical management. 15, 16 Studies of maternal short stature (defined as <155-cm) demonstrate an increased risk for cesarean, but the vast majority (>75%) of these women still deliver vaginally. 1719 Several studies of maternal foot size have found no correlation to mode of delivery.…”
Section: Commentmentioning
confidence: 99%
“…Although the pelvic inlet becomes contracted in response to nutritional stress during development, it is the pelvic midplane (Fig. l ) , the narrowest point in the birth canal, that interferes with the birth process in most populations (Sibley et al, 1992;Oxorn-Foote, 1986;Floberg et al, 1986Floberg et al, , 1987. The distance between the ischial spines, or bispinous diameter (BSD), defines the obstetric "plane of least dimensions" (Oxorn-Foote, 1986).…”
mentioning
confidence: 99%
“…Chalmers et al (1990) found a vaginal delivery rate of 66 to 94 per cent in women with adequate pelvimetry measurements. Parsons and Spellacy (1985) and Floberg et al (1986) found a correlation between clinical and radiological pelvimetry in up to 77 per cent of patients. Our vaginal delivery rate of 60 per cent with undiagnosed breech presentation confirms the usefulness of clinical assessment and does not support the case for routine immediate caesarean section.…”
Section: Discussionmentioning
confidence: 95%